2000
DOI: 10.1507/endocrj.47.359
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of Insulin in Leptin Maintenance. Profound Decrease in Serum Leptin by Octreotide Acetate in Insulinoma Subjects.

Abstract: Abstract. To further clarify the relationship between insulin and leptin, time course changes in plasma glucose, serum insulin and leptin levels were analyzed after subcutaneous administration of 100 pg octreotide acetate in two insulinoma subjects. Octreotide acetate induced a prompt decrease in serum insulin level, accompanied with an increase in plasma glucose in both patients. Following the decrease in serum insulin level, serum leptin concentrations were profoundly decreased by 66% and 44%, 8-12 hrs after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Although, we did not measure serum insulin levels, Stratton et al [2] reported that increments in leptin levels between day 0 and day + 1 were significantly related to the increase in insulin levels. Nakamura et al [19] demonstrated close association between insulin and leptin levels (r=0.899) in a patient, which were simultaneously measured during the baseline period by octreotide acetate treatment before and after resection of insulinoma. Increased serum insulin levels may thus be responsible for the increase in circulating leptin levels.…”
Section: Discussionmentioning
confidence: 97%
“…Although, we did not measure serum insulin levels, Stratton et al [2] reported that increments in leptin levels between day 0 and day + 1 were significantly related to the increase in insulin levels. Nakamura et al [19] demonstrated close association between insulin and leptin levels (r=0.899) in a patient, which were simultaneously measured during the baseline period by octreotide acetate treatment before and after resection of insulinoma. Increased serum insulin levels may thus be responsible for the increase in circulating leptin levels.…”
Section: Discussionmentioning
confidence: 97%
“…Ahren and Havel [31] reported that leptin inhibited insulin secretion in an in vitro study. Moreover, Nakamura et al [32,33] showed that insulin plays a crucial role in the maintenance of leptin secretion in humans. Our data support these results.…”
Section: Discussionmentioning
confidence: 99%
“…The function of SRIF receptors on adipocytes remains unknown. In vivo studies have demonstrated lowering of leptin levels by infusion of SRIF (50) and octreotide (51), an sst 2 /sst 5 -selective SRIF agonist; it is possible that SRIF regulates leptin secretion directly. We have detected sst 5 expression in perigonadal adipocyterich tissue isolated from WT mice and in 3T3-L1 adipocytes by RT-PCR.…”
Section: Fig 8 Changes In Insulin Sensitivity In Wt and Sst 5 Ko MImentioning
confidence: 99%